The Ternary and Quaternary Systems in Cu-based Shape Memory Alloys - Canbay, C. Aksu; Ozkul, I; Ahmed, H. Mustafa (Amer Inst Physics, 2019)
Shape memory alloy (SMA) is a unique useful material and has found increasing applications in many fields. The shape memory effect (SME) and pseudoelasticity, the two major properties of SMA associated with the thermal-induced or stress-induced reversible hysteretic phase transformation between austenite and martensite transformation. Those properties are important for use in both medical and industrial fields. The characteristic transformation temperatures and thermodynamic parameters of shape memory alloys can change by the variation of elements in the composition and also the proportions of the elements in the composition. Cu based-shape memory alloys also chosen for the fabrication due to easy production and low cost. The ternary Cu-20.82Al-3.53Fe (at%)and quaternary Cu-17.33Al-4.74Fe-2.08Mn (at%) shape memory alloys (SMAs) were produced by arc melting and characterized. The thermal analyses were performed by DSC at different heating/cooling rates and observed that the alloy samples exhibited the characteristic martensitic phase transitions that occurred at high temperatures. Also the thermal and kinetic parameters of sample such as enthalpy, entropy and equilibrium temperature were determined. The X-ray measurements of the samples were carried out at room temperature.
35th International Physics Congress of the Turkish-Physical-Society (TPS) -- SEP 04-08, 2019 -- Bodrum, TURKEY
Keywords: Microstructure